2019
DOI: 10.1016/j.csbj.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT Texture Analysis With Machine Learning for the Evaluation and Characterization of Cervical Lymphadenopathy

Abstract: Purpose To determine whether machine learning assisted-texture analysis of multi-energy virtual monochromatic image (VMI) datasets from dual-energy CT (DECT) can be used to differentiate metastatic head and neck squamous cell carcinoma (HNSCC) lymph nodes from lymphoma, inflammatory, or normal lymph nodes. Materials and methods A retrospective evaluation of 412 cervical nodes from 5 different patient groups (50 patients in total) having undergone DECT of the neck betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 46 publications
(69 reference statements)
2
60
0
3
Order By: Relevance
“…Texture analysis refers to an objective and quantitative set of metrics calculated for quantifying the textural patterns of images. Previous studies have showed radiomics features were associated with nodal involvement in oncologic imaging [7,12]. Herein, we studied primary tumor texture features of PDAC at preoperative CT by automatically extracting several quantitative parameters, which were compared according to the nodal involvement status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Texture analysis refers to an objective and quantitative set of metrics calculated for quantifying the textural patterns of images. Previous studies have showed radiomics features were associated with nodal involvement in oncologic imaging [7,12]. Herein, we studied primary tumor texture features of PDAC at preoperative CT by automatically extracting several quantitative parameters, which were compared according to the nodal involvement status.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-energy CT has been widely used recently [6]. Quantitative parameters derived from dual-energy CT data have proven to be useful for the diagnosis and nodal staging in several types of tumors [7][8][9][10]. However, the value of quantitative parameters from dual-energy CT in the preoperative diagnosis of LN metastasis in patients with pancreatic cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…an accuracy of up to 93% and 80% for distinguishing lymphoma and inflammatory from normal nodes, respectively, and of 92% for distinguishing benign and malignant lymph nodes [54]. However, the abovementioned studies focused on the differentiation between benign and malignant lesions; reports on the use of radiomics for differentiating between different types of malignant lesions are rare [31][32][33].…”
Section: Contrast Media and Molecular Imagingmentioning
confidence: 99%
“…e current trends in texture research involve the use of machine learning/deep learning to avoid the tedious process of manual operation and the accompanying uncertainty. Texture analysis based on dual-energy CT, full-field digital mammography, dual time 18 F-FDG PET/CT, and biparametric MRI can identify benign and malignant diseases with high efficiency (AUC fluctuates between 0.84-0.96 depending on the disease and analysis method) in studies using machine learning/deep learning [52][53][54][55]. e AUC in these studies did not significantly differ from that in our study, but the abovementioned studies focused on distinguishing between benign and malignant tumors.…”
mentioning
confidence: 99%
“…In the study, the morphological features of the lesions were excluded. An analysis was made only about the texture features of the lesions (21).…”
Section: Voi Segmentation and Radiomic Feature Acquisitionmentioning
confidence: 99%